Enhanced Removal of Dissolved Humic Acid from Water Using Eco‐Friendly Phenylalanine‐Modified‐Chitosan Fe3O4 Magnetic Nanoparticles. Issue 14 (15th April 2020) - Wang, Shujun; Li, Enze; Li, Yazhuo; Li, Jianfeng; Du, Zhiping; Cheng, Fangqin
Abstract: High‐efficient adsorbents with eco‐friendly and easy recycling features remain to be pursued in wastewater treatment. In this work, one green magnetic nano‐composite, phenylalanine‐modified‐chitosan Fe3 O4 (Fe3 O4 @chitosan@Phe), was prepared and its adsorption behavior for humic acid from water was investigated. Our results showed that the modified phenylalanine could promote the maximum adsorption quantites of humic acid by Fe3 O4 @chitosan@Phe than Fe3 O4 @chitosan, and the adsorption processing followed the pseudo second‐order kinetic model. Either the Langmuir or Freundlich isotherm model could not appropriately describe the adsorption processing, implying the adsorption process is more complex than typical monolayer, or multilayer adsorption. The functional groups (amidogen, phenyl) of phenylalanine could strengthen the interaction between Fe3 O4 @chitosan@Phe and humic acid molecules through electrostatic interaction, π‐π interaction, and hydrogen bonds. The Fe3 O4 @chitosan@Phe exhibited good reusability after running eight adsorption‐regeneration cycles. This work proposes a new strategy to design eco‐friendly magnetic adsorbents, which meets the requirement of modern green chemistry. Abstract : The phenylalanine‐modified‐chitosan Fe3 O4 magnetic nanoparticle (Fe3 O4 @chitosan@Phe) was synthesized and applied to remove humic acid from water. There existed electrostatic attraction, π‐π interaction, and hydrogen bonds between humic acid molecules and nanoparticle, which could strengthen the adsorption behavior. The adsorbent exhibited good adsorption capacity for HA in eight subsequent adsorption‐desorption cycles. This work might provide new insights into the design of functional adsorbent and enhance the treatment of complex wastewater.